2023
DOI: 10.1111/jgs.18499
|View full text |Cite
|
Sign up to set email alerts
|

Comparing quality of care outcomes between assisted living and nursing homes before and during the COVID‐19 pandemic

Abstract: BackgroundWhile assisted living (AL) and nursing home (NHs) residents in share vulnerabilities, AL provides fewer staffing resources and services. Research has largely neglected AL, especially during the COVID‐19 pandemic. Our study compared trends of practice‐sensitive, risk‐adjusted quality indicators between AL and NHs, and changes in these trends after the start of the pandemic.MethodsThis repeated cross‐sectional study used population‐based resident data in Alberta, Canada. Using Resident Assessment Instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Frustration with communication issues could be perceived as agitation and managed with medication. A recent study in Alberta (where this study was conducted) compared quality indicators for residents in SL and NH and found that antipsychotic use was consistently higher in SL residents than NH residents; this increased during the COVID-19 pandemic [ 30 ]. The focus of this study was not on the quality of clinical care that racialized and ethnoculturally diverse SL residents received; however, our findings do point to specific areas that warrant further qualitative research in tandem with an examination of available administrative health data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frustration with communication issues could be perceived as agitation and managed with medication. A recent study in Alberta (where this study was conducted) compared quality indicators for residents in SL and NH and found that antipsychotic use was consistently higher in SL residents than NH residents; this increased during the COVID-19 pandemic [ 30 ]. The focus of this study was not on the quality of clinical care that racialized and ethnoculturally diverse SL residents received; however, our findings do point to specific areas that warrant further qualitative research in tandem with an examination of available administrative health data.…”
Section: Discussionmentioning
confidence: 99%
“…What little research there is on SL in Canada has found that SL residents are similar to NH residents in terms of age, cognitive impairment, chronic conditions, and functional limitations, yet SL facilities have fewer services and less staffing resources lack the staffing resources of NHs [ 23 , 25 29 ]. Recent studies comparing NH and SL in Alberta before and during the COVID-19 pandemic found troubling differences in the settings, including higher rates of antipsychotic use, pain, and depressive symptoms in SL compared to NHs [ 30 ]. A recent literature review examined the needs of older people with dementia from culturally and linguistically diverse backgrounds but none of the included studies specifically examined residents in SL facilities [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis was a comparison of the pandemic period against the 2 most recent historical years and did not test for year-over-year trends. Interrupted time series analysis by Hoben et al 3 supports Dr. Quail’s argument that the inappropriate use of antipsychotic medications increased in the years leading up to the pandemic in Alberta. However, in alignment with our own findings, the rate of that increase accelerated significantly during the pandemic period.…”
mentioning
confidence: 89%
“…Reports that inhabitants of nursing homes were one of the neglected groups of the pandemic, with high COVID-19-associated mortality and social isolation rates [53][54][55]. The indicated reductions in on-site visits of inhabitants of nursing homes and assisted living institutions hint at a reduced quality of psychiatric care.…”
Section: Reduced Visits In Nursing Homes and Assisted Living Institut...mentioning
confidence: 99%